Ricostruzione 3D e caratterizzazione dei materiali delle statue Moai dell'Isola di Pasqua - Marsella, Maria; Sonnessa, Alberico; Orlando, Luciana; Soddu, Pierluigi; Margottini, Claudio; Spizzichino, Daniele (GEOmedia, 2009)
Integration of advanced geomatic and geophysics surveys for characterization of Moai statues in Easter Island (Chile) Between 15 and 27 July 2008 a field campaign aimed at collecting topographical and geophysical data useful for geometric reconstruction and material characterization of a Moai Statue was carried out on the Ester Island (Rapa Nui,Chile). The scientific activity, conducted by a team of researchers of Sapienza University of Rome (DITS) and of the Institute for Environmental Protection and Research (ISPRA), is part of the "MOAI AL MONDO” Project, coordinated by Marenostrum Foundation and sponsorized by Louis Vuitton Malletier. which promote the dissemination of the cultural and archeological heritage of Easter Island's people to Europe and to the world.